ATTITUDES TOWARD PRISONERS, AS REPORTED EMPLOYEES BY THE COMPANIES WICH IS EXECUTED COMMUNITY SENTENCE - Đurđević, Sanja; Krivokapić, Žilijeta; Šapić, Rosa; Vićentić, Sreten (Specijalna edukacija i rehabilitacija, 2016)
Whether alternative penalties served by offenders in the community will be successful can also largely depend on the general attitude in the workplace where the offender will be serving his penalty. This study, conducted in Belgrade, Serbia, was aimed to determine the inclination and factor structure of attitudes towards prisoners and ex-prisoners and their correlation with age and education of respondents. The sample consisted of males of the general population (N=78), employed in companies where offenders are serving community sentence. The study also considers the association between attitudes and the age and education of the respondents. The Scale for Attitudes toward Prisoners and Ex-Prisoners was used in the study. Results of research showed that respondents in general had positive attitude toward prisoners. On the Scale of Attitudes, the greatest mean value is held by a statement "I would employ ex-prisoner"(AM=3,81) with which 34.60% of respondents “agree strongly”. Negatively formulated statements have a somewhat lower arithmetic mean (ranging from AM = 2.71 to AM = 2.99). With most negatively formulated statements, the frequency of statements “agree strongly” are low, ranging from 7.70% to 15.60%.Factor analysis of the attitude scale indicated three respectable factors which were named: Rejection, Trust, and Perception of Penalty. The correlation between the demographic variables of age and education, and the expressed attitudes shows there was no significant correlation (p=0,93; p=0,86). The findings of the study have an important impact on practical psychosocial issues, such as that of preparing the community to accept prisoners serving alternative punishments, as well as theoretical questions regarding the understanding of the structure, cause, origin, function, and form of attitudes toward prisoners. Keywords: attitudes, prisoners, community, community service penalties